New Zionism and the foreign policy system of Israel - Seliktar, Ofira (Routledge library editions. Israel and Palestine, 2015)
The invasion of Lebanon was the culmination of an extraordinary change which New Zionism created in Israel's foreign policy system. This book, first published in 1986, examines how New Zionism came to dominate Israeli politics and it investigates the implications of this new ideology for the future of the Middle East. The author agrees that after the creation of the State of Israel, the belief system of the evolving society gradually changed. After the Six-Day War the ideology of Socialist Zionism became increasingly discredited and replaced by the New Zionist quest for Eretz Israel. Hardened by the harsh experience of the continuing Arab-Israeli conflict and enhanced by the threatening image of the enemy, the political culture in Israel became less tolerant and more receptive to the language of New Zionism. As a result, Begin's Likud came to power in 1977 and quickly changed the whole basis of Israel's foreign policy. Instead of the cautious pragmatism of Socialist Zionism the Begin government pursued the 'grand design' that had enjoyed a long tradition in Revisionist thinking. Although General Sharon was responsible for the actual conduct of the war, it was the New Zionist propensity to use military force to introduce a new order in the Middle East which was responsible for the invasion. The book suggests that it is still too early to assess the full impact of the war in Lebanon on New Zionism. Although the war failed to validate any of the 'grand design' tenets of New Zionism, the violent Shiite response in Southern Lebanon may serve to strengthen the New Zionist hard line. This could hasten the annexation of the occupied territories as the final stage of turning the State of Israel into the Land of Israel.